Complete man, love in truth, and living in diversity, in two ancient Sundanese manuscripts - Ajie, Sophan; Sutarno, Alfonsus; Bolo, Andreas Doweng; Yusandi, Yusandi (FISIP UIN SGD Bandung, 2025)
This study examines the moral and philosophical messages of two ancient Sundanese manuscripts, namely Amanat Galunggung and Sanghyang Siksa Kandang Karesian, then relates them to Unpar's Spirituality and Basic Values ​​known as SINDU. Data were collected using a qualitative research strategy through in-depth interviews and literature studies. Then, they were analyzed based on the theory of intertextuality, namely by examining the messages of each manuscript, comparing them, and seeing the correlation or interdependence between the two. The results of the study show that the two ancient Sundanese manuscripts above are full of humanitarian messages that remain relevant and significant for modern human life. The concept of SINDU, which was born more recently, finds its basis and foundation in the teachings that have long existed in the two ancient manuscripts. This study also reveals the existence of basic human needs for humanitarian values ​​throughout their lives, whether in the past, present, or future. Moral and philosophical values ​​are needed by humans in an effort to make themselves humane and divine. Contribution: It underscores the persistent human need for moral and philosophical guidance across time, enriching both academic understanding and practical applications in promoting humane and divine human development.